HUBUNGAN PENGETAHUAN DAN SIKAP ORANG TUA DENGAN PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK - Eva Yuliani; Boby Nurmagandi; Irfan Irfan; Weny Anggraini Adhisty; Ika Muzdalia; Ninin Handayani (Bina Generasi : Jurnal Kesehatan, 2023)
Background: Sexual violence against children is a very serious problem. One way that can be done to prevent it is to involve parents as the closest people to children who have a very important role in preventing sexual violence with an adequate level of knowledge and attitude. Object: To find out whether there is a relationship between parents' knowledge and attitudes with the prevention of sexual violence in children aged 6-12 years in Rangas. Methods: Descriptive analytic with a cross sectional study approach, the number of respondents is 41 people using the Purposive Sampling sample selection technique. Data collection using a questionnaire. Results: data analysis concluded that 70.7% of respondents had good knowledge, 29.3% of respondents had sufficient knowledge and 95.1% of respondents had good attitudes. Statistical test results for knowledge obtained a value of ρ = 0.734 > α = 0.05, for attitudes obtained a value of ρ = 0.453 <α = 0.05. Conclusion: knowledge and attitudes of parents do not have a significant relationship with the prevention of sexual violence in children, because the level of education of parents is still low so that attitudes are not formed that can be shown to families, especially children, do not have the ability to shape behavior to conduct early sexual education in children and considers that giving explanations to children about the positive and negative impacts of sexual health is taboo.